A modalidade na competência V do ENEM: a aula de produção textual como prática de letramento crítico sob a perspectiva sistêmico-funcional - Faria, Fabiane Dalben De [UNIFESP] (2019)
Research in the literacy area (STREET, 1984, 1988, 2011, COPEL, KALANTZIS, 1993; HALLIDAY, 1996; BARTON, HAMILTON, 1998, 2000; SHOR, 1999; ROJO, 2009; MENEZES DE SOUZA, 2011; JANKS , 2016) aim to size the development complexity of literacy practices and events that encourage, through writing, a more critical stance, allowing, in addition to language proficiency, a training that promotes the active participation of individuals in society. As a way of providing subsidies for the understanding of the relationship between language and literacy, this research is based on a corpus of 301 essays produced by 60 students who, in 2017, attended the 2nd and 3rd years of high school and college preparation courses in two private schools. The research participants were organized into two groups: Group 1, with 21 students from a school located in Campinas and; Group 2, with 39 students from a school located in Indaiatuba. Data was collected from a Textual Production Workshop organized in the schools‟ counter-shifts. The general objective of this research, based on the analysis of the corpus, is to develop pedagogical practices that allow the teaching of adequate language conventions for textual production, establishing connections between school learning and other domains of students' lives and (i) understand how the Sydney School‟s Teaching and Learning Cycle (TLC) theory (ROSE; MARTIN, 2012) and their relationship with literacy practices can help students in the development of their textual production; (ii) identify the language realizations that demonstrate compliance with the competence V required by the exam in the essay proposals based on the ENEM and (iii) understand which meanings are construed through these realizations. The theoretical and analytical perspective is based on the Systemic Functional Grammar, theorized by Halliday and Hasan (1989), Halliday (1994), Eggins (2004) and Halliday and Matthiessen (2014). Data analysis is guided by the Interpersonal Metafunction and its Modality System (HALLIDAY; MATTHIESSEN, 2014; EGGINS, 2004), specifically in the identification of the modal operators used by the students in their texts. With this panorama, the proposed analysis development covers two main levels: (i) the first level is related to literacy events and practices developed throughout the offered Workshop, from the TLC levels and stages, and its contribution to the students‟critical literacy; and (ii) the second level is related to the grammatical aspect, in which the modal operators in the texts are analyzed. For the analysis of the operators in the students' essays, AntConc‟s Concordance and Word List tools were used to quantify the modal operators‟ frequency. The results show that (i) after all the stages of CEA had been developed, there was an improvement in the students' textual production and in the presentation of social intervention proposals; (ii) students use modal auxiliary verbs, must being the most frequent, and also interpersonal metaphors (it is necessary, it is needed...) aiming to modulate the social intervention proposals and (iii) the frequency of modal operators that indicate high commitment with the intervention proposals was increased during the development of the themes, revealing that students began to adopt more critical and protagonist positions in their textual productions, confirming, as proposed by Halliday (1996), that mastering language assumes an important role in the development of literacies.